Ordnung für die Wahl der Pfarrgemeinderäte vom 06.01.1995 - Katholische Kirche Diözese Speyer Bischof (1995)
Aus: KABl SP 88 (1995), 319-324
Keywords: Pfarrgemeinderat; Wahlordnung; Partikularrecht; Speyer; Norm